Mixed-mode fracture behaviors of AISI 1045 and AISI 5140 steels in compressor crankshafts – Part I: Mode I-III. (March 2020) - Nie, Defu; Chen, Xuedong; Wu, Qiaoguo
Highlights: A new loading device and specimens were developed to investigate mixed-mode I-III fracture. Cleavage fracture features are shown under mode I loading, but shear features under other loading. Crack propagated in pre-crack plane under mode I loading while in max shear stress plane for others. A new I-III fracture criterion is proposed and crack deflection angle is related to loading angle. Abstract: Mixed-mode fracture occasionally occurred in compressor crankshafts made of AISI 1045 and AISI 5140 steels due to complex stress in service. Therefore, a new loading device and specimens were developed to investigate such problems. This study mainly focused on mixed-mode I-III fracture behaviors. It was found that under mode I loading condition, both AISI 1045 and AISI 5140 steels showed almost linear load-displacement responses and cleavage fracture features, and cracks propagated in the pre-crack planes. Under the other loading conditions, nonlinear portions of load-displacement curves became obvious, fracture surfaces had ductile features except that the ductile to brittle transition took place under the mixed-mode I-III (22.5°) loading condition, and cracks propagated in the planes of the maximum shear stress. Based on the obtained results, a criterion for mixed-mode I-III fracture was proposed and the predicted results were consistent with the experimental data.